2021
DOI: 10.1093/jnci/djaa220
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of young-onset colorectal cancer with a focus on years approaching screening age: A population-based longitudinal study

Abstract: Background With recent evidence for the increasing risk of young-onset colorectal cancer (yCRC), our objective was to evaluate the incidence of yCRC in one-year age increments, particularly focusing around the screening age of 50 years. Methods We conducted a longitudinal study using linked administrative health databases in British Columbia, Canada including a provincial cancer registry, inpatient/outpatient visits, and vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 13 publications
0
25
0
1
Order By: Relevance
“…Abualkhair et al found a drastic increase of CRC patients as individuals shifted from the 49 to 50 years old, suggesting a large number of preclinical undetected yCRC cases that might be detected with a lower age for guideline-based screening [ 28 ]. Our group similarly found a steady increase through this same age transition [ 5 ]. Modeling of CRC screening strategies in Canada suggest that stool-based screening would yield 20 additional life-years per 1000 people screened along with a 10% increase in colonoscopy demand, compared to ages 50 to 74 [ 27 ].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Abualkhair et al found a drastic increase of CRC patients as individuals shifted from the 49 to 50 years old, suggesting a large number of preclinical undetected yCRC cases that might be detected with a lower age for guideline-based screening [ 28 ]. Our group similarly found a steady increase through this same age transition [ 5 ]. Modeling of CRC screening strategies in Canada suggest that stool-based screening would yield 20 additional life-years per 1000 people screened along with a 10% increase in colonoscopy demand, compared to ages 50 to 74 [ 27 ].…”
Section: Discussionmentioning
confidence: 78%
“…The US Preventative Services Task Force recently lowered the age for screening for average risk patients to age 45 [ 26 ]. Results on the effectiveness of decreasing the age for eligibility for screening has been mixed [ 5 , 27 , 28 ]. Abualkhair et al found a drastic increase of CRC patients as individuals shifted from the 49 to 50 years old, suggesting a large number of preclinical undetected yCRC cases that might be detected with a lower age for guideline-based screening [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of CRC in men and women under the age of 50 in the United States continued to increase at a rate of 2% annually from 1995 to 2016. Registries show an increased incidence of CRC among young adults aged 20-39 years, although the total number of cases in this age group remains signi cantly lower than that of adults aged 50 years and older [17][18][19][20][21][22][23][24][25][26]. Most cases of colorectal cancer occur in people with no family history of colorectal cancer or a predisposing disease, as our research con rms.…”
Section: Personal Medical Historymentioning
confidence: 72%
“…Essa neoplasia é incomum antes dos 40 anos, com aumento significativo da incidência entre as idades de 40-50. Embora dados mais recentes do banco de dados de Vigilância, Epidemiologia e Resultados Finais (SEER) dos Estados Unidos e outros registros de câncer ocidentais sugiram que a incidência esteja aumentando no grupo de menores de 50 anos e diminuindo nos mais velhos 7,10,12 ; neste estudo observou-se que a média de idade continua acima de 50 anos. Esse aumento está sendo notado predominantemente por cânceres do lado esquerdo e do reto em particular.…”
Section: Discussionunclassified